Beyond the fireground: injuries in the fire service. Issue 4 (23rd November 2011) - Poplin, Gerald S; Harris, Robin B; Pollack, Keshia M; Peate, Wayne F; Burgess, Jefferey L
Abstract : Background: Although firefighting and emergency medical services are high-risk professions, few studies have identified the aetiology of injury in the fire service beyond the fireground. Methods: Data were collected for work-related injuries in a medium-sized metropolitan fire department. In a descriptive study, the factors explored included the nature of injury, agent, mechanism, body location, environment, abbreviated injury scale (AIS), functional capacity index (FCI) and lost time status. Results: From 2004 to 2009, the annual injury incidence rate averaged 17.7 per 100 employees. One-third of all injuries (32.9%) resulted from physical exercise activities, while patient transport, training drills and fireground operations resulted in 16.9%, 11.1% and 10.2% of injuries, respectively. For all job operations, sprains and strains were the most prevalent type of injury (40.2–85.2%), followed by contusions and lacerations (7.7–26.1%). The third most common injury was related to the conventional hazards of the individual job operation. Most injuries (n=862, 95.6%) were minor in severity, while 4.3% of injuries were classified as having some impedance of normal function (FCI 3). Moderate injuries (AIS 2) were infrequent, but comprised a greater proportion of fireground injuries (8.7%) than the other activities (1.0–4.1%); however, lost time injuries were more frequent for patient transport (46.1%) than other operations (22.0–29.1%). Conclusions: Physical exercise, patient transport and training activities were responsible for a greater percentage of injuries than fireground operations. Focused efforts to improve the characterisation of risks during these more diverse set of work processes should help guide the development of salient strategies for injury prevention.